Impact of two organic fertilizers (mycorhize and poultry manure) associated with pollinators insects on growth and yields of Zea mays L. at Baré (Littorale Region-Cameroon) (JOURNAL OF ADVANCES IN AGRICULTURE, 2025)
Field of maize was conducted during the rainy season in 2021 and 2022 in Baré (Littorale Region - Cameroon) aiming to contribute to the improvement of the yield of maize by combining two organic fertilizers and pollinators insects. The main factor was pollination with two levels (plants left on free pollination and plants isolated from insects). The secondary aspect was fertilization with four points, mycorhize-poultry manure, mycorhize, poultry manure and control. The growth parameters, the diversity and foraging activity of pollinators insects, the influence of organic fertilizers and pollinator insects were evaluated on the yields. The results showed that the plants located on the plots treated with mycorhize-poultry, mycorhize and poultry manure showed significant growth on the number of the leaves (p